Vehicle load loading method for the fatigue analysis of long-span suspension bridges with straddling slings - Chai, Jin-Ling; Wang, Yong; Xia, Lian-Xue; Li, Sheng-Li (Frontiers in Mechanical Engineering, 2025)
In this study, the bridge structure is subjected to fatigue analysis. While the vehicle load application method for medium- and small-span bridges is relatively well-established, methods for fatigue analysis of large-span bridges under vehicle loads are still limited. This paper summarizes the vehicle load application method for fatigue analysis of medium- and small-span bridges in foreign countries. Based on the sling of a large-span suspension bridge, a vehicle load application method for sling fatigue analysis in long-span suspension bridges is proposed. The proposed method is compared and analyzed, and relevant conclusions are drawn, which provides a reasonable approach for the fatigue analysis of cable structures in long-span bridges.